EVALUASI INTRODUKSI KEDELAI VARIETAS BROMO DI EKCAMATAN KLEGO, KABUPATEN BOYOLALI - Joko Triastono; Sri Widodo; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
One of the technological components to attain soybean productivity increase is using a modern varieties. This research aims to evaluate the introduction of a new modern variety of soybean, such as Bromo variety, in Klego Subdistrict, Boyolali District, Central Java on first crop season 1998/1999 season. The objectives of the research were to know the effect of the introduction Bromo variety of soybean on soybean productivity, profit and employment, as well as to know the production efficiency.This research used a cross-sectional data of 50 sample farmers consisted of 25 Bromo variety farmers and 25 Local variety farmers. To know the effect of Bromo variety introduction on productivity, profit and employment, it was used regression analysis with Ordinary Least Square (OLS) method. To test the production efficiency of inputs use was used allocative efficiency test.The results showed that Bromo variety introduction were able to increase productivity 501.71 kg/ha, to increase profit Rp 1,852,370/ha and to increase employment 14.25 mandays/ha. The allocative efficiency test showed that the farmers of Bromo variety and the farmers of Local variety hadn't allocated their inputs efficiently yet. To increase the soybean production, Bromo variety can be recommended